Sistem Pakar untuk Menentukan Status Gizi pada Balita dengan Menggunakan Metode Certainty Factor - Rindi Devi; Fajar Ratnawati (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Nutrition is an important factor in the growth and development of toddlers. Good nutritional status has a significant impact on their health and future. On the other hand, nutritional issues in toddlers can lead to serious consequences, with the risk of causing death. However, many parents struggle to determine their child's nutritional status due to limited knowledge caused by a lack of education on nutrition, financial constraints, busy work schedules, and infrequent visits to healthcare facilities for nutritional check-ups. As a solution, this research develops an expert system to determine the nutritional status of toddlers using the Certainty Factor method. The Certainty Factor method is chosen for its ability to generate a level of certainty in diagnoses, helping parents understand their child's nutritional condition. Based on the research results, this system has been implemented with an accuracy rate of 96.15%. Therefore, this expert system can serve as an accurate and reliable tool, especially for parents in determining their toddler's nutritional status.